(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Employee performance plays an important role in increasing the success of a company, so it is very important to increase employee competence, empowerment and work commitment, This study aims to determine the effect of increasing employee competence, empowerment and work commitment on employee performance at the Regional Water Supply Company (PDAM) Gianyar Regency. The total samples in this study as many as 69 respondents. The data analysis techniques used are multiple linear regression analysis, determination coefficient test, t test and F test. The results of this study are Competence has a positive and significant effect on employee performance at the Regional Water Supply Company (PDAM) Gianyar Regency. Empowerment has a positive and significant effect on employee performance at the Regional Water Supply Company (PDAM) of Gianyar Regency. Organizational commitment has a positive and significant effect on employee performance at the Regional Water Supply Company (PDAM) of Gianyar Regency. Competence, empowerment and organizational commitment have a positive and significant effect on employee performance at the Regional Water Supply Company (PDAM) Gianyar Regency. Suggestions that can be given are to increase the provision of training to increase employee competence and ability, involve employees while working and provide bonuses and compensation to increase work commitment so that it affects employee performance.